Time and Frequency Response of Non-uniform Overhead Lines Under Corona - Mohamed M. Saied (International Journal of Electrical Machine Analysis and Design, 2024)
This study presents an efficient and direct technique for determining both the time and frequency responses of non-uniform overhead power transmission lines operating under corona conditions. The assumed-line's non-uniformity is due to the conductors’ sag. Expressions will be presented for the location-dependent line surge impedance and the unevenly distributed lines’ electrical parameters. The analysis starts with solving the relevant system of differential and algebraic equations, subject to the boundary conditions. Their numerical solution is possible through the application of the software program Mathematica, leading to Laplace-domain expressions for the line’s voltage and current distributions, in terms of the location and the Laplace operator location’s. The line’s input impedance can then be derived from the voltage and current at the sending end. The line’s resonance frequencies can also be easily determined. A numerical Laplace inversion using the Hosono algorithm will lead to the corresponding voltage and current equations in the time domain. The effect of the line length, the number of towers, the intensity of the corona discharge as well as the loading condition is taken into consideration. The suggested approach is applied to a typical multi-span overhead high voltage transmission line. A special test case study is investigated to validate the suggested approach and computer code.
Keywords: Hosono algorithm; Simulation; differential equations; electromagnetic; frequency response; high voltage lines; inverse laplace transform; laplace transform; mathematica; numerical solutions; parametric ND solve; transients